The Effect of a Combined Basketball and Strength Training Program with the Body Weight on Performance in Adolescent Basketball Players - Kosmatos, Γεώργιος; Gerodimos, Βασίλειος; Karatrandou, Νάντια; Goudas, Μάριος; Tsiokanos, Αθανάσιος (Inquiries in Physical Education and Sport, 2008)
The aim of this study was to explore whether a systematic, combined basketball and strengthening training program using the body weight, can improve the performance of adolescent basketball players. The sample consisted of 45 young boys, aged from 11 to 13 years old (11.9±0.7yrs), who were divided into 3 groups: the combined training group (CG), the basketball training group (BG) and a control group (COG). The CG performed a basketball training combined with a strengthening program, while the BG followed only a basketball training program and the COG did not perform regular training. The BG participated in a 3-month basketball training program while the intervention for the CG involved a 3-month program combining basketball training as well as abdominal and dorsal exercises, submersions, push-ups, projections and rises of the feet, jogging backwards and isometric squat-positions. The children’s performance in push-ups, submersions, abdominals, mobility, speed, medical ball throwing, endurance, the lower limbs extensor muscles’ force and in jumping capacity was evaluated just before and right after the end of the application of the 3-month program. For the statistical elaboration of the data a two way ANOVA analysis of variation was used (group x measure 3x2) with repetitive measuring of the factor “measurement” as well as tukey’s analysis whenever necessary. From the elaboration of the results, it was found that there were statistically significant interactions among the factors “measurement” and “groups” in all the tests apart from the mobility and retrogression test. In conclusion, comparing the efficiency of the two programmes, the CG’s training program was more efficient, in relation to the other two groups, regarding the improvement in strength of the upper part of the body in young basketball players.